Sex and ancestry related differences between two Central European populations determined using exocranial meshes - Musilová, Barbora; Dupej, Ján; Brůžek, Jaroslav; Bejdová, Šárka; Velemínská, Jana (Forensic science international, 2019)
Assessing sex and population affinity is an important part of the process of biologically identifying unknown human remains, and the skull is usually one of the best structures for assessing both these components of the biological profile. Population affinity is known to be a hugely important variable when estimating sex because the manifestation of sexually dimorphic traits, body size or social and behavioural habits differs across populations. Therefore, for forensic purposes, the estimation of ancestry is a necessary step in the identification of bone remains. The present study improves on the results of a previously developed virtual method using the exocranial surface for sex estimation and assessing population affinity. The ability to assess these components of the biological profile was successfully tested on 208 individuals from two recent European populations. The original classifier was based on geometric morphometric analyses (CPD-DCA, PCA, SVM) and was able to assess the sex of individuals belonging to one French population with an accuracy exceeding 90 % Musilová et al. [1]. To improve the reliability of the method, the Czech population sample was added to the dataset, yielding the highest accuracy of 96.2 %; using the combined dataset, the reliability of the method was 91.8 %. Secondly, we used the same method utilizing inter-population differences to classify individuals based on the shape of the skull. The greatest accuracy rate was 92.8 %, which makes our method a promising tool for sex estimation and assessing population affinity.
Keywords: dospělí; Support Vector Machine; Female; zobrazování trojrozměrné; Imaging, Three-Dimensional; Adult; mladý dospělý; ženské pohlaví; Adolescent; Reproducibility of Results; strojové učení; lidé; Francie; Forensic Anthropology; Sex Determination by Skeleton; Skull; reprodukovatelnost výsledků; určení pohlaví podle kostry; Male; Aged; Czech Republic; Machine Learning; Young Adult; Principal Component Analysis; France; Česká republika; lidé středního věku; lebka; support vector machine; analýza hlavních komponent; senioři; mužské pohlaví; White People; běloši; soudní antropologie; Middle Aged; mladiství; Humans